The cultural legacy of the frontier lands of Vinalopó (Alicante, Spain) and their tourist use – impossible mission? - Martínez Puche, Antonio; Martínez Puche, Salvador (Ethnologies, 2016)
“Frontier tourism” or tourisme de partage is a genuine typology of tourism which has these four features: space (geographic), time (historic), experience (motivations and behaviours) and sharing cultural heritage (material or immaterial). The border lands of Alto Vinalopó (Alicante-Spain) have a paradoxical and dual element in the sense that they operate as a territory with common customs and traditions which share many similarities with other territories, but at the same time they show a number of contrasts and peculiarities.Reorganized now as potential tourist attractions, these deep-rooted ethnographic displays are becoming consumable products, which are struggling to find a differential position in the leisure business.This article is aimed at illustrating this process, analysing its sociocultural, economic and promotional variables by considering a particular event: the Moors and Christians festival in Villena. These ancient celebrations convey their own values and signs of identity which have also served to stimulate and diversify the local economy. Besides, after being officially declared in 2015 a national tourist attraction, with the “4th September, All Mad” campaign, this festival has generated challenges, uncertainties and opportunities for tourist development which will demand the right creative strategies and economic management to succeed.